EFFECT OF GIVING MIXED INSECTICIDE CARBOFURAN IN COW FECES TOWARDS CONSUMPTION RATE AND ASSIMILATION EFFICIENCY EARTHWORM Pheretima javanica Gates - Nofyan, Erwin; Lamin, Syafrina; Patriot, Innocenthya Tygra (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2016)
Research about “Giving a mixture of Insecticide Carbofuran in cow feces to the Rate of Consumption and the Efficiency of Absorption on Land Worm Pheretima javanica Gates was held on June to August 2016 at Animal Physiology Laboratorium, Biology Department, Faculty of Mathematics and Science, Sriwijaya University, Indralaya, Ogan Ilir, South Sumatera. The purpose of this research is to learn the effect of Insecticide Carbofuran to the rate of consumption and the efficiency of absorption on land worm Pheretima javanica Gates. Contribution of this research gives the information to farmer about the effect of insecticide carbofuran to non-target animal, especially to land worm Pheretima javanica Gates. This research used Completely Randomized Design with 6 treatments and 5 times repetition. Treatment that was given to sample are the insecticide carbofuran with concentration of 0 % (control); 0.1% ; 0.2 % ; 0.3 % ; 0.4 % ; 0.5 %. Data analysis was using Varians Analysis. If there was real difference then data analysis continued with The Duncan Test on level of confidence of 95%. The results of this research show us that several concentration of insecticide carbofuran have the real effect to the average of consumption rate and the efficiency of absorption. The lowest average of consumption rate on land worm Pheretima javanica is on concentration of 0,5 % (0.23 ± 0.02 mg/g day) and the highest average of consumption rate on land worm Pheretima javanica is on concentration of 0% (control) (2.53 ± 0.05 mg/g day). The lowest average of absorption efficiency on land worm Pheretima javanica is on concentration of 0 % (control) (40.78 ± 2.56 % )and the highest average of absorption efficiency on land worm Pheretima javanica is on concentration of 0,5 % (70.76 ± 3.67 %). Keywords: carbofuran, the rate of consumption, the efficiency of absorption, Pheretima javanica Gates.